An international comparison of the utilisation of and outcomes from minimal access surgery for the treatment of common abdominal surgical emergencies - Tukanova, Karina (Surg Endosc, 2019)
BACKGROUND: Minimal access surgery (MAS) has suggested improvements in clinical outcomes compared to open surgery in several abdominal elective and emergency surgeries. The aims of this study were to compare England with the United States in the utilisation of MAS and mortality from four common abdominal surgical emergencies. METHODS: Between 2006 and 2012, the rate of MAS and in-hospital mortality for appendicitis, incarcerated or strangulated abdominal hernia, small or large bowel and peptic ulcer perforation were compared between England and the United States. Univariate and multivariate analyses were performed to adjust for differences in baseline patient demographics. RESULTS: 132,364 admissions in England were compared to an estimated 1,811,136 admissions in the United States. Minimal access surgery was used less commonly in England for appendicitis (odds ratio (OR) 0.27, 95% CI 0.267–0.278), abdominal hernia (OR 0.16, 95% CI 0.15–0.17), small or large bowel perforation (OR 0.33, 95% CI 0.32–0.35) and peptic ulcer perforation (OR 0.93, 95% CI 0.87–0.99). In-hospital mortality was increased in England compared to the United States for all four conditions: appendicitis (OR 2.11, 95% CI 1.66–2.68), abdominal hernia (OR 3.25, 95% CI 3.10–3.40), small or large bowel perforation (OR 3.88, 95% CI 3.76–3.99) and peptic ulcer perforation (OR 3.09, 95% CI 2.94–3.25). In England, after adjustment for patient demographics, open surgery was associated with increased in-hospital mortality for abdominal hernia (OR 1.80, 95% CI 1.26–2.71), small or large bowel perforation (OR 1.59, 95% CI 1.37–1.87) and peptic ulcer perforation (OR 2.31, 95% CI 1.91–2.82). CONCLUSIONS: Minimal access surgery was performed less commonly and in-hospital mortality was increased in England compared to the United States for common abdominal surgical conditions. Therefore, strategies to enhance adoption of MAS in emergency conditions in England need to be optimised and include appropriate patient selection and improved surgeon MAS training. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00464-019-06980-y) contains supplementary material, which is available to authorised users.